Isolasi dan Uji Bakteri Lipolitik dalam Mendegradasi Minyak Pada Limbah Cair Kelapa Sawit di Kebun Marihat, Pematang Siantar - Chairunnisa Chairunnisa; Riyanto Riyanto; Abdul Karim (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
Research on isolation and testing of lipolityc bacteria in oli degradation of palm oil mill efluent (POME) at Marihat, Pematang Siantar. This research was conduteted at the Bioproses Laboratory, Palm Oil Research Institute, Medan. The purpose of this study was to obtain lipolytic bacterial isolates and determine the ability of these lipolytic bacteria to degrade oil. Isolation of bacteria using a selective medium lipolytic. Data of the analysis that were 8 isolates of lipolytic bacteria in pallm oil mill effluent and the potential to degrade oil with index activity of lipolytic isolates. The higgest lipolityc isolate index with code BL-1 is 2,78, and the lowest lipolytic index BL-8 is 1,40.